Indoor Location Tracking Using Time of Arrival Estimation Method - Sreekumar, Nandita; Sebastian, Shoney (International Journal of Sensors Wireless Communications and Control, 2020)
Background & Objective: Location-based services enable collection of location-oriented information which finds use in various fields. Methods: With its utility found in so many applications, various localization techniques are adopted to improve these services. One such property of a signal which is used for these estimations is known as ‘Time of Arrival’ property. The ‘Time of Arrival’ property of a signal is the time difference for a signal to go from the transmitter to the receiver. The most common application is to navigate through places, finding or tracking your personal belongings, targeted advertisements by knowing the nearby popular places and various other services like augmented reality gaming among others. Results & Conclusion: Through this paper, we demonstrate a method to track the location of a mobile sensor node using Trilateration algorithm with the help of Time of Arrival (ToA) property of signals. The time of arrival of packets at each node is recorded and data collected from the simulation of a wireless sensor network for this experiment is spread across various distributions to find the optimum statistical inference.
Keywords: trilateration